A study of prisms and therapy in attention loss after stroke (SPATIAL): A feasibility randomised controlled trial. (March 2023) - Longley, Verity; Woodward-Nutt, Kate; Turton, Ailie J.; Stocking, Katie; Checketts, Matthew; Bamford, Ann; Douglass, Emma; Taylor, Julie; Woodley, Julie; Moule, Pam; Vail, Andy; Bowen, Audrey
Objective: Investigate feasibility and acceptability of prism adaptation training for people with inattention (spatial neglect), early after stroke, during usual care. Design: Phase II feasibility randomised controlled trial with 3:1 stratified allocation to standard occupational therapy with or without intervention, and nested process evaluation. Setting: Ten hospital sites providing in-patient stroke services. Participants: Screened positive for inattention more than one-week post-stroke; informal carers. Occupational therapists participated in qualitative interviews. Intervention: Adjunctive prism adaptation training at the start of standard occupational therapy sessions for three weeks. Main measures: Feasibility measures included recruitment and retention rates, intervention fidelity and attrition. Outcomes collected at baseline, 3 weeks and 12 weeks tested measures including Nottingham Extended Activities of Daily Living Scale. Acceptability was explored through qualitative interviews and structured questions. Results: Eighty (31%) patients were eligible, 57 (71%) consented, 54 randomised (40:13, +1 exclusion) and 39 (74%) completed 12-week outcomes. Treatment fidelity was good: participants received median eight intervention sessions (IQR: 5, 12) lasting 4.7 min (IQR: 4.1, 5.0). All six serious adverse events were unrelated. There was no signal that patients allocated to intervention did better than controls. Twenty five of 35 recruited carers provided outcomes with excellent data completeness. Therapists, patients and carers found prism adaptation training acceptable. Conclusions: It is feasible and acceptable to conduct a high-quality definitive trial of prism adaptation training within occupational therapy early after stroke in usual care setting, but difficult to justify given no sign of benefit over standard occupational therapy. Clinical trial registration: https://www.isrctn.com/ Ref ISRCTN88395268.